Herbal medicine use during breastfeeding: a cross-sectional study among mothers visiting public health facilities in the Western area of Sierra Leone - Peter Bai James; Angela Isata Kaikai; Abdulai Jawo Bah; Amie Steel; Jon Wardle (BMC, 2019)
Abstract Background The use of medications, including herbal medicines during breastfeeding is always a concern among women. Currently, there is no published evidence on whether Sierra Leonean women use herbal medicine during breastfeeding. This study investigates the prevalence, correlates and pattern of herbal medicine use during breastfeeding. Methodology We conducted a cross-sectional study among 378 current breastfeeding mothers visiting public healthcare facilities within the Western area of Sierra Leone. Descriptive statistics and logistic regression analysis were used for data analysis. Results Over a third of mothers (n = 140, 37.0%) used herbal medicine during breastfeeding. However, very few herbal medicine users (2.1%, n = 3) used herbal medicine to augment breastfeeding. Dietary changes were the most common method used to increase breast milk supply (93.9%, n = 355) with cassava leaves sauce and tubers being the most common dietary addition. Mothers with children more than six months old were more likely to use herbal medicine than mothers with younger children (OR:1.8; CI:1.13-2.85,p = 0.013). Among herbal medicine users, only 11.4% (n = 16) disclosed their herbal medicine use to their conventional healthcare providers. Conclusion The use of herbal medicine among breastfeeding mothers attending public health facilities in the Western area of Sierra Leone is common. Whilst this use is not usually specific to increasing breast milk supply, our study indicates that herbal medicines may be used to 'cleanse' initial breast milk.